Pengaruh Masa Kadaluarsa dan Penggunaan Berbagai Ekstrak Bahan Organik Terhadap Viabilitas dan Vigor Benih Semangka (Citrullus vulgaris Schard.) - Ainun Marliah; Mariani Nasution; Syaiful Azmi (Jurnal Agrista, 2010)
Effect of Expired Time and Use if Various Organic Matter Extract on Viability and Vigor Water Melon SeedABSTRACT. The experiment was conducted to study the effect of expired time and use of various organic matter extract on viability and vigor water melon seed. The experiment was conducted in completely randomized design with two factors and three replication. Factors of expired time: 3, 6 and 9 months. Factor of organic matter extract: coconut extract, mature tomato extract, juvenile corn extract, and mature banana extract. The results indicated that expired time was significantly different on viability and vigor water melon seed. The best expired time treatment for viability and vigor water melon seed 3 months. Organic matter extract was significantly different on viability and vigor water melon seed. The best organic matter extract treatment for viability and vigor water melon seed was mature tomato extract. There was significantly different interaction between expired time and use of various organic matter extract on growth potency.